The Influence of Product Design, Price, and Promotion on Purchasing Decisions on Phinisi Ship Tour Packages in Labuan Bajo and Service Recovery as Mediation: (Case study at PT. Komodo Escape Prawara) - Nanut, Senita; Junaedi, I Wayan Ruspendi; Santoso, R Tri Priyono Budi; Komalasari, Yeyen (Eastasouth Institute, 2024)
Labuan Bajo is one of the tourist areas visited by many tourists, of course, competition between companies is very tight. Company management competes to offer the best service to please tourists. This research aims to analyze the influence of product design, price, and promotion on the decision to purchase Phinisi boat tour packages in Labuan Bajo and service recovery as mediation. The number used in this research was 36 through saturated samples. Data collection was carried out using a questionnaire. Technique analysis data using SEM-PLS. The research results show that product design has a positive and significant effect on service recovery for phinisi boat tour packages in Labuan Bajo. Price has a positive and significant effect on service recovery for phinisi boat tour packages in Labuan Bajo. The promotion has a positive and significant effect on service recovery for Phinisi boat tour packages in Labuan Bajo. Product design has a positive and significant influence on the decision to purchase a Phinisi boat tour package in Labuan Bajo. Price has a positive and significant effect on the decision to purchase a phinisi boat tour package in Labuan Bajo. The promotion has a positive and significant effect on the decision to purchase a phinisi boat tour package in Labuan Bajo. Service recovery partially mediates the influence of product design on the decision to purchase a Phinisi boat tour package in Labuan Bajo. Service recovery partially mediates the influence of price on the decision to purchase a Phinisi boat tour package in Labuan Bajo. Service recovery partially mediates the influence of promotions on the decision to purchase Phinisi boat tour packages in Labuan Bajo.